2023
DOI: 10.3389/feart.2023.1188737
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary deformation relating to episodic seepage in the last 1.2 million years: a multi-scale seismic study from the Vestnesa Ridge, eastern Fram Strait

Abstract: Seafloor hydrocarbon seepage is a natural fluid release process that occurs worldwide on continental shelves, slopes, and in deep oceanic basins. The Vestnesa sedimentary ridge in the eastern Fram Strait hosts a deep-water gas hydrate system that became charged with hydrocarbons ∼2.7 Ma and has experienced episodic seepage along the entire ridge until a few thousand years ago, when seepage activity apparently ceased in the west but persisted in the east. Although it has been documented that faults and fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…The dating of sedimentary cores points to a correlation between the glacial cycles and increased seepage directly after the glacial maxima; therefore, several authors proposed glacial tectonics as the dominant force behind the seepage activity cycles (Himmler et al., 2019; Schneider et al., 2018). These observations cannot however explain why a similar group of seafloor structures (pockmarks), further west on the crest of the ridge, connected to the recent (>8,000 years ago) seepage activity, is presently dormant (Consolaro et al., 2015; Cooke et al., 2023; Plaza‐Faverola et al., 2015). It was previously suggested that the spatial variation in seepage activity is driven predominantly by the tectonic forces from the seafloor spreading at the MR and KR (Plaza‐Faverola & Keiding, 2019; Plaza‐Faverola et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dating of sedimentary cores points to a correlation between the glacial cycles and increased seepage directly after the glacial maxima; therefore, several authors proposed glacial tectonics as the dominant force behind the seepage activity cycles (Himmler et al., 2019; Schneider et al., 2018). These observations cannot however explain why a similar group of seafloor structures (pockmarks), further west on the crest of the ridge, connected to the recent (>8,000 years ago) seepage activity, is presently dormant (Consolaro et al., 2015; Cooke et al., 2023; Plaza‐Faverola et al., 2015). It was previously suggested that the spatial variation in seepage activity is driven predominantly by the tectonic forces from the seafloor spreading at the MR and KR (Plaza‐Faverola & Keiding, 2019; Plaza‐Faverola et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Gas hydrates with the underlying free gas accumulations are identified from seismic reflection data along the entire length of the Vestnesa Ridge (Goswami et al., 2015; Hustoft et al., 2009; Petersen et al., 2010; Plaza‐Faverola et al., 2017; Singhroha et al., 2016, 2019). Presently documented seepage is contained within the eastern part of the ridge crest, but past seepage activity on the western segment of the system is well documented in sediments, seismic data, and bathymetry (Cooke et al., 2023; Consolaro et al., 2015; Plaza‐Faverola et al., 2015; Vogt & Crane, 1994). Current seepage activity from pockmarks occurs at the termination of sub‐seafloor fluid flow fault systems (Plaza‐Faverola et al., 2015).…”
Section: Deep Marine Fluid Flow Systems In the Fram Straitmentioning
confidence: 99%
“…The SMTZ at western Vestnesa Ridge is found >2 m in the pockmark of core site HH16-550GC and >10 m outside of the pockmark at site HH16-543GC (Laier et al, 2017) (Figure 1C; Figure 4K,L). Results from studies combining seismic data and pore pressure data from Vestnesa Ridge have indicated that the western part at present mostly experience gas seepage as slow and diffusive, while in the eastern part numerous faults and fractures from sediment deformation also allow gas to escape in the gas phase, i.e., termed advective seepage (Plaza-Faverola et al, 2015;Cooke et al, 2023). At Vestnesa Ridge the thick Holocene deposits in the western part effectively filled the pockmarks and slowed the seepage of methane.…”
Section: Depositional Patterns and Seepage Of Gas 421 Organic And Ino...mentioning
confidence: 99%